Preliminary phytochemical screening, antimicrobial potentials and GC-MS analysis of Secamone afzelli Rhoem (asclepiadaceae) leaves extracts (2020)
Secamone afzelli is used ethno-medicinally as remedies for stomach, colic and gastro-intestinal tract infections. This study screened the hexane, ethyl acetate and ethanol extracts of S. afzelli leaves for phytocompounds, antimicrobial activity and identified bioactive compounds in the most active extract using Gas Chromatography Mass Spectrometry (GC-MS) analysis. S. afzelli (200mg) leave was extracted by soxhlet apparatus using three solvents (hexane, ethyl acetate and ethanol) and the phytochemicals determined. Antimicrobial susceptibility and minimum inhibitory concentrations (MICs) was determined by agar-diffusion and agar-dilution methods respectively against selected resistant bacterial and fungal clinical isolates. The most active of the three crude extracts was analysed by GC-MS for bioactive compounds identification. Presence of carbohydrates, anthraquinone, glycosides, proteins, tannin, phenolic compounds and steroids were determined. The three extracts (hexane, ethyl acetate, and ethanol extracts) had antibacterial (Range of inhibition zone = 10 to 18 mm and MICs 12.5 to 200 mg/mL) but no antifungal activity. The ethanol extract was the most active with 29 bioactive compounds including piperazine, phytol, leucine methyl ester, N-methyl-N-(1-methylethyl)- 1Pentanamine, 7-propyl-pyrrolizin-1-thione and 4,5-dimethylnonane. The antibacterial activity and arrays of bioactive compounds detected in S. afzelli leaves suggest that the plant may be a good source of novel antimicrobial compounds.